2007
DOI: 10.1093/brain/awl364
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome and prognostic factors of frontal lobe epilepsy surgery

Abstract: Frontal lobe epilepsy (FLE) surgery is the second most common surgery performed to treat pharmacoresistant epilepsy. Yet, little is known about long-term seizure outcome following frontal lobectomy. The aim of this study is to investigate the trends in longitudinal outcome and identify potential prognostic indicators in a cohort of FLE patients investigated using modern diagnostic techniques. We reviewed 70 patients who underwent a frontal lobectomy between 1995 and 2003 (mean follow-up 4.1 +/- 3 years). Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
308
7
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(356 citation statements)
references
References 56 publications
27
308
7
14
Order By: Relevance
“…4 Our MRInegative cohort (comprised of temporal and extratemporal cases) had seizure-free rate of 59% at 12 months, this percentage is consistent with other studies from our center and can be anticipated to drop as follow-up durations increase. 10,34,35 Overall, we found that positive pathology in surgical specimen positively associated with seizure-free outcome at 6 months, but not at 12 months. This finding is consistent with the hypothesis that immediate postoperative seizure recurrence may indicate a mislocalization and/or incomplete resection of the active epileptic focus, whereas long-term recurrence may be attributed to other factors such as the natural history of the disease and the postsurgical development of secondary epileptogenesis.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…4 Our MRInegative cohort (comprised of temporal and extratemporal cases) had seizure-free rate of 59% at 12 months, this percentage is consistent with other studies from our center and can be anticipated to drop as follow-up durations increase. 10,34,35 Overall, we found that positive pathology in surgical specimen positively associated with seizure-free outcome at 6 months, but not at 12 months. This finding is consistent with the hypothesis that immediate postoperative seizure recurrence may indicate a mislocalization and/or incomplete resection of the active epileptic focus, whereas long-term recurrence may be attributed to other factors such as the natural history of the disease and the postsurgical development of secondary epileptogenesis.…”
Section: Discussionmentioning
confidence: 54%
“…[5][6][7][8] Despite substantial efforts, the lack of a lesion on MRI has consistently been shown to be one of the predictors for surgical failure. 9,10 Therefore, MRI-negative patients are usually considered unfavorable surgical candidates 4 and are often denied epilepsy surgery. Yet, surgical resection can be effective in well-selected patients with no visible MRI abnormality.…”
mentioning
confidence: 99%
“…In effect, both time and brain area of seizure occurrence are diffi cult to predict [ 103 ]. Interestingly, for cases where antiepileptic medication does not exhibit seizure-suppressing effects, a possible therapy is to remove parts of the temporal lobe or to disconnect specifi c projections that allow for seizure spreading [ 104 ].…”
Section: Componentsmentioning
confidence: 99%
“…Up to 72% of patients with MR imaging-negative epilepsy who had surgery were found to have FCD, and others have nonspecific findings such as gliosis on histopathology. [9][10][11][12][13] Identification of an anatomic abnormality has important therapeutic and prognostic implications, with considerably better outcomes in patients with an identifiable lesion than in those with MR imaging-negative localization-related epilepsy.…”
mentioning
confidence: 99%